How to Deal with Non-Dominant Languages – Metalinguistic Discourses on Low German in the Nineteenth Century - Langer, Nils; Langhanke, Robert (Linguistik Online, 2013)
This paper discusses nineteenth-century metalinguistic discussions of Low German, an authochthonous of Northern Germany, which, having lost its status as a written language suitable for formal discourse during the Early Modern period, has since been reduced to the spoken domain. During the nineteenth century the language was on the verge of enjoying a revival, with original poetry being published and extensive discussions as to whether Low German ought to play a role in formal education. As this article shows, this discussion was intense and controversial. Comparing the views of Klaus Groth, the leading proponent of Low German in the second half of the nineteenth century, with the internal debates amongst school teachers - hitherto never discussed by the scholarly literature – this article demonstrates the intellectual and ideological split felt by these educational practioners in their views of Low German: on the one hand, they recognise the cultural value of Low German as the historical language of the North and the native language of the pupils they teach, on the other hand they agree with each other that the language of education and science, as well as national unity, can only be High German. We hope to show with our discussion not only how very similar modern thinking on the use of Low German is to these historical discussions but also how the status and perception of many regional and minority languages across the world has been subject to the same or very similar thoughts and pressures.